INTERAKSI SOSIAL ANTARA ORANG LANJUT USIA DENGAN MASYARAKAT - Murlis Murlis (Ensiklopedia Social Review, 2020)
An interaction process is based on various factors, among others, factors of imitation, suggestion, identification and sympathy. These factors can move independently or in a combined state. If each is examined more deeply, the imitation factor, for example, has a very important role in the process of social interaction. One of the positive aspects is that imitation can encourage a person to obey the rules and values that apply. However, imitation may also result in negative things where for example, what is imitated are deviant actions. In addition, imitation can also weaken or even kill the development of one's creative power. The suggestion factor takes place when someone gives a view or an attitude that comes from himself which is then accepted by the other party. So this process is actually almost the same as imitation, but the benchmarks are different. The suggestion can take place because the receiving party is hit by emotions that impede rational power. Perhaps the suggestion process occurs if the person giving the view is an authoritative person or perhaps because of his authoritarian nature. It is also possible that suggestions occur due to causes that give views or attitudes the largest part of the group concerned, or society. Likewise for the social interactions of the elderly with family members.